KOMUNIKASI SEBAGAI DETERMINAN UTAMA IMPLEMENTASI MANAJEMEN KINERJA TIM - Tarsisius Timuneno (Universitas Nusa Cendana, 2015)
The shifting in management style that prioritize the design of teams work within the company, requiring for specific approaches in managing the team. The requirement will makes the TeamPerformance Management as one of the most rational approach in order to optimize the role andperformance of the team, and to support the achievement of objectives and to increase the enterprisescompetitiveness in global business era today. Team Performance Management is continuous processof communication in a partnership between the manager and the managed team. It is embodiedthrough three phases i.e. planning and team performance agreement phase, continuousperformances communication and team performance evaluation meeting. That three phases willmark the implementation of Team Performance Management in each companies and affirmexplicitly the importance of communication as a main determinant. Horizontal communicationchannel with decentralized network is a special type of team communication that has most part insupporting the creation of true team and high-performance team. Keywords: team, team performance management, communication Sejak pertengahan dekade 1980-an istilah “tim” menjadi sangat populer dan